2017
DOI: 10.5624/isd.2017.47.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of impacted maxillary third molars: A cone-beam computed tomographic study of the position and depth of impaction

Abstract: PurposeThe classification of impacted maxillary third molars (IMTMs) facilitates interdisciplinary communication and helps estimate the degree of surgical difficulty. Thus, this study aimed to develop a 3-dimensional classification of the position and depth of impaction of IMTMs and to estimate their prevalence with respect to gender and age.Materials and MethodsThis cross-sectional retrospective study analyzed images in sagittal and coronal cone-beam computed tomography (CBCT) sections of 300 maxillary third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…One of the ERR risk factors discussed in the literature is patient age. Eruptive tooth movement does not stop after root formation is completed, and these teeth continue to exert mechanical pressure on adjacent second molars, thereby creating conditions for ERR progression [21]. Therefore, it can be assumed that the odds for ERR may increase with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ERR risk factors discussed in the literature is patient age. Eruptive tooth movement does not stop after root formation is completed, and these teeth continue to exert mechanical pressure on adjacent second molars, thereby creating conditions for ERR progression [21]. Therefore, it can be assumed that the odds for ERR may increase with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on interobserver reproducibility regarding the maxillary third molar seen in PAN and CBCT are non-existing since the studies either did not mention the number of observers or reported only results made in consensus, and interobserver reproducibility was not calculated. [8][9][10][11][12] On the other hand, studies on assessment of pathology related to the mandibular third molar are available in the literature. [19][20][21][22][23] In a previous study assessing resorption in PAN and CBCT of mandibular third molars, the average percentage of observer accordance was 83% for PAN and 72% in CBCT among four observers.…”
Section: Observer Reproducibility Of Pan and Cbctmentioning
confidence: 99%
“…Studies currently available on the use of CBCT for maxillary third molars have reached F&T-level 2 and 3 according to the hierarchical model of efficacy assessing the accuracy of the method. [8][9][10][11][12] Previous studies at Level 2 investigated the angulation and impaction depth of impacted maxillary third molars in both PAN and CBCT. 8,9 Both studies found that buccal inclination was the most common position in the transversal plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No postoperative complications including infection or injury of the IAN or lingual nerve were reported. The demographic data of the patients and the results of analyzing the in uencing factors based on the status and radiographic signs of the mandibular M3 and the distribution of cases are presented in Table 1 [23][24][25].…”
Section: Resultsmentioning
confidence: 99%